2022
DOI: 10.3390/foods11152282
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR Assays for the Strain-Specific Identification and Enumeration of Probiotic Strain Lacticaseibacillus rhamnosus X253

Abstract: Probiotics are universally recognized for their health benefits, despite the fact that their effects depend on the strain. Identification and enumeration of probiotic strains are required prior to evaluating their effectiveness. Lacticaseibacillus rhamnosus X253 is a potential probiotic strain with antioxidant capacity. Comparative genomics and single nucleotide polymorphisms (SNPs) were used to identify a strain-specific locus within the holA gene for strain X253 that was distinct in 30 different L. rhamnosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This reflects a shift in the position of the repetitive sequences in the genomes of the three strains, and the actual PCR also produced varied electrophoretic patterns depending on the strain. Third, since the reproducibility tests for samples before and after subculturing can reflect that the PCR is not the non-specific response (Cangelosi et al, 2004;Zhao et al, 2022), it was confirmed using samples before and after In this study, designed rep-PCR showed 7 identical groups and statistical correlation with the VNTR profiles (Cramer's V value of 0.814) (Figure 4). There were two sets of serial isolated M. intracellulare strains; the first set (KBN12P06800 in group 7 and KBN12P06801 in group 7 from a patient A) showed same rep-PCR group and shared on 22/23 VNTR loci (96%) (Figure 4).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This reflects a shift in the position of the repetitive sequences in the genomes of the three strains, and the actual PCR also produced varied electrophoretic patterns depending on the strain. Third, since the reproducibility tests for samples before and after subculturing can reflect that the PCR is not the non-specific response (Cangelosi et al, 2004;Zhao et al, 2022), it was confirmed using samples before and after In this study, designed rep-PCR showed 7 identical groups and statistical correlation with the VNTR profiles (Cramer's V value of 0.814) (Figure 4). There were two sets of serial isolated M. intracellulare strains; the first set (KBN12P06800 in group 7 and KBN12P06801 in group 7 from a patient A) showed same rep-PCR group and shared on 22/23 VNTR loci (96%) (Figure 4).…”
Section: Discussionsupporting
confidence: 63%
“…This reflects a shift in the position of the repetitive sequences in the genomes of the three strains, and the actual PCR also produced varied electrophoretic patterns depending on the strain. Third, since the reproducibility tests for samples before and after subculturing can reflect that the PCR is not the non-specific response ( Cangelosi et al, 2004 ; Zhao et al, 2022 ), it was confirmed using samples before and after subculturing that designed rep-PCR has a greater level of reproducibility (Pearson similarity 95–98%) than previous published rep-PCR ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation